Factors influencing self-sealing of sclerotomy performed under gas tamponade in 23-gauge transconjunctival sutureless vitrectomy - Takashina, Hirotsugu (Dove Medical Press, 2014)
BACKGROUND: The purpose of this study was to investigate factors influencing self-sealing of sclerotomy performed under gas tamponade in 23-gauge transconjunctival sutureless vitrectomy. METHODS: This study was a retrospective review of 84 patients (84 eyes) who underwent 23-gauge transconjunctival sutureless vitrectomy under gas tamponade by a single surgeon. At the end of surgery, the sclerotomy was massaged to promote self-sealing. Factors influencing massage time were examined using multiple regression analysis. Independent variables were age, surgical time, vitreous incarceration, intraocular manipulation, and axial length. RESULTS: Significant factors were intraocular manipulation and vitreous incarceration in the examination of all sclerotomies, age only in the examination of infusion sites, and vitreous incarceration only in the examination of manipulation sites. CONCLUSION: In sclerotomy performed with gas tamponade using 23-gauge transconjunctival sutureless vitrectomy, intraocular manipulation influenced self-sealing of sclerotomy the most, followed by vitreous incarceration, and then age.